1989
DOI: 10.1063/1.101808
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline diamond growth in thin films deposited from a CH4/Ar rf plasma

Abstract: Observation of single-crystal diamond growth in thin films obtained from the rf decomposition of a CH4/Ar plasma is reported. The films were deposited on Si substrates which were kept at 20 °C. Polycrystalline diamond grains are seen over the entire film. Single-crystal diffraction patterns obtained from larger grains all show {111} twinning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…Nanodiamond crystals of different sizes, ranging from 5 to 15 nm, were found within an amorphous carbon matrix. While both Amaratunga's and Gruen's nanodiamond crystals, obtained at 13.56 MHz and 2.45 GHz, respectively, were seen over their entire film surface [11], our nanodiamond crystals are not uniformly distributed and they are found, by direct observation using TEM at low magnification, to cover between 10 and 20% of the deposited film surface. Such distinct distribution might be explained in terms of the combined effect associated to the substrate temperature and the ion energy distributions corresponding to the different plasma excitation frequencies (2.45 GHz, 13.56 MHz and 35 kHz) of the various systems used by different research groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanodiamond crystals of different sizes, ranging from 5 to 15 nm, were found within an amorphous carbon matrix. While both Amaratunga's and Gruen's nanodiamond crystals, obtained at 13.56 MHz and 2.45 GHz, respectively, were seen over their entire film surface [11], our nanodiamond crystals are not uniformly distributed and they are found, by direct observation using TEM at low magnification, to cover between 10 and 20% of the deposited film surface. Such distinct distribution might be explained in terms of the combined effect associated to the substrate temperature and the ion energy distributions corresponding to the different plasma excitation frequencies (2.45 GHz, 13.56 MHz and 35 kHz) of the various systems used by different research groups.…”
Section: Resultsmentioning
confidence: 99%
“…Following both the experimental results and theoretical predictions by Aisenberg and Chabot [13] and Lifshitz et al [14], respectively; Amaratunga et al [11] explain their uniform nanodiamond crystal distribution, grown from a 13.56 MHz excited CH 4 /Ar (98%) plasma on a low temperature (20 8C) substrate, by the impact of Ar þ energetic ions coming from the plasma. According to Lifshitz et al [14], diamond film nucleation is especially aided at certain (optimum) ion energies that were specifically tuned in Amaratunga's experiment [11].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to microwave plasma, direct current (dc) [19], hot filament [20], magnetron sputtering [21], and radio frequency (rf) plasmas [22][23][24] have been utilized for nanocrystalline diamond deposition. Amaratunga et al [23,24], using CH 4 /Ar rf plasma, reported that singlecrystal diffraction patterns obtained from nanocrystalline diamond grains all show {1 1 1} twinning.…”
Section: Conventional Microwave Pe-cvdmentioning
confidence: 99%